Objective analysis of microtia reconstruction in Indian patients and modifications in management protocol - Mohit Sharma; Raghuveer Reddy Dudipala; Jimmy Mathew; Abhijeet Wakure; Krishnakumar Thankappan; Deepak Balasubramaniam; Subramania Iyer (Indian Journal of Plastic Surgery)
Introduction: An ideal ear, with representation of all anatomic landmarks, is the aim of any reconstructive surgeon embarking on reconstructing the ear in a microtia patient. The literature is abundant with the description of techniques, but these have been reported mainly in Caucasian and Oriental population. There have been very few publications on results in the population belonging to the Indian subcontinent. In spite of strictly adhering to the recommended techniques of reconstruction, the results obtained in these patients have often been marred by problems that are not reported with the Oriental or Caucasian populations. This may necessitate a relook into the management strategy of these cases. Hindering the assessment of the results, their reporting and auditing the improvement obtained by such change in the management strategy, is the lack of a standardized method for assessment of the outcome. Hence, an attempt was made in a series of patients who underwent microtia reconstruction to assess the outcome using a new tool based on the attained definition of anatomical components of the reconstructed pinna. Further effort was made to document the modifications in the technical execution of the reconstruction during the period of the study. Materials and Methods: A retrospective review of 44 patients and a prospective analysis of 11 patients, who underwent ear reconstruction for microtia from December 2003 to September 2014 at a tertiary care teaching hospital, was undertaken. Taking a cue from Nagata’s description of an ’ideal reconstructed ear’ which should show all the anatomical components, we developed an objective grading system to assess our results. The technique had undergone several changes during these years combining the principles of three universally accepted methods, that is, those described by Nagata, Brent, and Firmin. These changes, as well as the reasons behind them, were documented. Results: On objectively measuring and analysing the replication of normal morphologic characteristics of the reconstructed ears, we documented progressive improvement of our results. Good or excellent results could be achieved in 70% of cases in the second group compared to a poor outcome in more than 2/3rd of the cases carried out during the initial period. Based on these results and the changes adopted in our practice we propose suggestions for management of microtia cases in the Indian population. Conclusions: An objective, weighted grading system has further enabled us to critically evaluate the outcomes and to further improve upon the existing results. Our amalgamation of the salient features of the established techniques as well as changes made based on our experience has enabled us to get good results more consistently in our attempts at microtia reconstruction. We believe that the adoption of such amalgamated methods will be more suitable in Indian patients.